(untitled) (Heritage, 2021)
Modern language teaching ​​is oriented towards the use of new technologies, and in this regard it is necessary to work on the development of digital literacy, both for students and teachers. Knowing how to find, select, analyze and adequately use digital information are important segments of digital literacy. In this regard, in foreign language teaching, digitally literate teachers and students can further contribute to their own development, learning and acquisition of foreign languages. With the help of digital literacy, students are able to use digital tools, digital information as well as create online projects in foreign languages. However, in order for students to adequately work on their tasks in an online environment, teacher moderators are needed who strive for continuous improvement in this field, who cultivate positive attitudes towards the use of new technologies and recognize their pedagogical value. Therefore, the focus of this paper is, first, on defining the concept of digital literacy, on pointing out the connection between digital literacy and learning and teaching foreign languages, on student work and the role of teachers in the digital environment, as well as on research results.